ABOUT BLESSING B YPATRIARCH TIКHON OF WORKS OF CULTURE WORKERS FOR PROTECTION AND RESTORATIONS OF ANCIENT SACRALART. - I.KYZLASOVA (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article interprets facts about Patriarch Tikhon's blessing on conservation ofsome wonder(working icons, the Commission for conservation of art and antiquity mon(uments (I.Grabar, A.Anisimov, G.Chirikov – the deed of 1918) and Board for protectionof the Holy Trinity and Sergius Lavra (I.Bondarenko, priest P.Florensky, J.Olsufjev,1919)